2020
DOI: 10.3390/molecules25061360
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intramuscular Naloxone Dose on Mu Receptor Displacement of Carfentanil in Rhesus Monkeys

Abstract: Naloxone (NLX) is a mu receptor antagonist used to treat acute opioid overdoses. Currently approved doses of naloxone to treat opioid overdoses are 4 mg intranasal (IN) and 2 mg intramuscular (IM). However, higher mu receptor occupancy (RO) may be required to treat overdoses due to more potent synthetic opioids such as fentanyl and carfentanil that have entered the illicit drug market recently. To address this need, a higher dose of NLX has been investigated in a 5 mg IM formulation called ZIMHI but, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Contrarily to morphine, which has antagonistic interactions with 5HT 3A receptors [ 32 ], interaction of fentanyl with 5HT 1A and 2A receptors might lead to additional toxicity due to serotonin syndrome, especially in combination with other drugs active on the serotonin system [ 33 ]. This might explain why rescue therapy with naloxone (receptor antagonist) are noneffective, or less effective than what expected [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily to morphine, which has antagonistic interactions with 5HT 3A receptors [ 32 ], interaction of fentanyl with 5HT 1A and 2A receptors might lead to additional toxicity due to serotonin syndrome, especially in combination with other drugs active on the serotonin system [ 33 ]. This might explain why rescue therapy with naloxone (receptor antagonist) are noneffective, or less effective than what expected [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The preservation of biological activities during the conjugation process is the apogee of this platform, offering significant advantages over traditional drug development and the possibility of improved therapeutic outcomes for complex diseases. C-192, despite its complex structure and a limited number of animal subjects, demonstrated stable physical properties and acceptable pharmacokinetic profiles [65][66][67][68], highlighting the clinical feasibility of UniStac. C-192 presents an ideal PK profile, making it suitable for weekly administration in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of these differences for treating OIRDs have been investigated in preclinical studies and systems pharmacology modeling of the relationship between plasma naloxone levels and μ-opioid receptor occupancy. One study in rhesus monkeys found a direct correlation between the plasma levels achieved with higher doses of IM naloxone and the degree of μ-opioid receptor blockade observed in the basal ganglia and thalamus with an 0.06-mg/kg naloxone IM dose producing a mean 56% occupancy by naloxone of the μ-opioid receptors in the basal ganglia and 47% in the thalamus ( 54 ). Doses of 0.14 and 0.28 mg/kg increased the percentage of occupied receptors to 74 and 75% in the basal ganglia and 65 and 74% in the thalamus, respectively.…”
Section: Treatment Of Oirdmentioning
confidence: 99%